The Effectiveness of Learning Method Moddeling The Way to The Results of Learning Fiqh Class 2 at Modern Islamic Boarding School Darussalam Gontor for Girls 2 Academic Year 2021/1443 - Agus Budiman; Ai Kokom Komala Sari (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Fiqh is a very important to be studied, understood and applied by learners, because fiqh discusses the subjects of Islamic law based on the Qur'an and hadith. The value of Fiqh subjects in the 2nd grade of Modern Darussalam Gontor Putri Kampus II still presents learning outcomes that are not optimal, so researchers are interested in conducting research with the application of Modelling The Way method. Modelling the way is an interactive learning method used by educators to stimulate the liveliness, courage and learning intensity of learners. In order to improve learning outcomes, researchers tried to examine the effectiveness of the method modelling the way on student learning outcomes on grade II G Fiqh material at modern islamic boarding school darussalam gontor for girls 2.The purpose of this study is : (1) knowing the pre-test value of the experimental class and the control class. (2) knowing the post test value for the experimental class and the control class. (3) knowing the effectiveness of the method modelling the way on the results of studying fiqih student grade II KMI at Modern Islamic Boarding School Darussalam gontor for girls 2 Academic year 2021/1443.This research was conducted by quantitative research method-experiment approach Pretest-Posttest Control Group Design. The population in this study was all grade 11 KMI at modern islamic boarding school darussalam gontor for girls 2, with a total of 40 samples, using proportional Sample Random Sampling techniques. consisting of 20 people in the experimental grade and 20 people in the control grade. The researcher collects data by test questions. The researcher's data analysis used the u-test formula (Mann Whitney), with the help of SPSS 16. The study obtained the conclusion that : (1) The average results of the experimental grade pre-test value of 5.90 and the control grade of 5.80, these results show that the two groups have the same or balanced ability as evidenced by the results of the Mann Whitney test of Sig. (2-tailed) 883 > 0,05. (2) With the average post test grade of experiment class 9.40 and control class of 8.15, these results showed a significant difference between the use of modeling the way method and conventional evidenced by mann whitney test results of Sig. (2-tailed)0,000<0,05. (3) The use of the method of modeling the way proved effective in fiqh learning with the acquisition of Mann Whitney's u-test formula value of Sig. (2-tailed)0.000 <0.05. Based on the conclusion, the researchers put forward several suggestions, that : (1) For teachers, to be more innovative in creating learning methods. The application of the method of modeling the way can be used as one of the input materials in the learning process so that later it can improve student learning outcomes, especially in fiqh material, generally in other subject matter. (2) For students, it is expected to be serious in following the learning process, pay attention to the material presented by the teacher, and it is hoped that students can repeat the subject matter that has been studied at home. . <w:LsdException Locked=